RELEVANSI TRADISI NYADRAN DALAM PERSPEKTIF MUSLIM PURITAN - Maulida, Rahma; Istiqomah, Zain Rozana; Subarkah, Zar’i (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The spread of Islamic teachings was carried out by the scholars in their own ways as the Wali Songo used cultural acculturation as an instrument for the acceptance of Islamic teachings by the community. However, the Puritan group disagrees with the moderate group who agrees with the method of cultural acculturation. This study examines the perspective of the Puritans and their attitudes towards cultural acculturation, especially in the Nyadran tradition. This study is a qualitative study that uses an approach through the library research method, namely through the process of collecting data from various literatures such as journals and other scientific papers, then processing the data from the collected data, the next process is data analysis and finally concluding the data as the core of the results of this study. The results of the study show that there is a rejection of the Puritans towards the Nyadran tradition with the argument that there are elements of bid'ah, shirk and also khurofat in the syncretism between culture and religion. In addition to rejection, the Puritans also synergize in voicing the purification of religion from the culture or traditions of society, this is their attitude in facing acculturation or syncretism between culture and religion in the midst of society.